Artificial Intelligence: A Driving Force In Advancing Patient Centricity (Journal of Pharmaceutical Negative Results, 2023)
One striking change that has occurred in what fundamentally drives businesses today is the journey towards a ‘customer-focused’ approach. The healthcare industry has followed the same suit. Today’s patients or beneficiaries expect the liberty of choice and the more personal or individualistic these choices become, the better. In the current digital age, patients are more informed and educated than ever. They know their rights and are voicing their concerns on global platforms. Healthcare Industry has no option but to meet the demands and needs of the patients. Therefore, the current healthcare landscape is undergoing essential modifications, attributed to the pressure created to meet patient-centered goals. With the advent of advanced technologies and globalization, the healthcare ecosystem is trying its best to meet their demand at the global level, where Artificial Intelligence (AI) is playing the central role. The wave of AI has been increasing in the industry day by day. The current article articulates how AI and data science are transforming life sciences and explains how this sector is deploying these tools to meet patient centricity.